Recent Advances in Solvent‐Free Asymmetric Catalysis. Issue 13 (27th May 2019) - Tavakolian, Mina; Vahdati‐Khajeh, Saleh; Asgari, Sepideh
Abstract: It is well‐known that solvent is one of the most important factors that affect chemical reactions. This factor is more noticeable and impressive in the asymmetric reactions where the effective interaction of reactants and the creation of a uniform chiral environment is necessary. Nevertheless, when reactions are carried out in the absence of solvent, some privileged advantages such as easy work up, short reaction time, lack of waste solvents, and following the green chemistry principles, are appeared. Therefore, according to the importance of asymmetric synthesis and green chemistry, solvent‐free asymmetric catalysis can act as a considerable and necessary subject in synthetic chemistry. In this review, we have a survey on the solvent‐free asymmetric synthesis by the use of either homogeneous or heterogeneous chiral catalysts. Abstract : The best solvent is no solvent ! By considering the importance of green chemistry and enantioselective synthesis, solvent‐free asymmetric catalysis can be considered as a bridge between these two important fields in synthetic chemistry. In this context, the main objective of this review is study on solvent‐free asymmetric reactions using chiral organocatalysts and supported chiral catalysts.